Studi Experimental Pengaruh Variasi Bukaan Katup Pada Aliran Fluida Terhadap Performa Simulator Turbin Pelton - Hartono, Yudi; Amin, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
The Pelton turbine is a microhydro device that can convert kinetic energy into electrical energy with the help of water flow. A valve is a piping system that functions to regulate, direct and control the rate of fluid flow by opening and closing the fluid flow. The steps used in this research include design methods, tool testing methods, data collection methods, and data analysis methods. The aim of this research is to determine the effect of varying valve openings of 30°, 60° and 90° on the values of rotational speed, torque, turbine power, generator power and system efficiency from the Pelton turbine simulator. From the test results and data processing, it was found that a 90° valve opening had better rotational speed, torque, turbine power and generator power, as well as system efficiency compared to 30° and 60° valve openings